Rheology of vacuum-concentrated kalamansi juice and sugar-concentrated juice mixed with hydrocolloid - Ocasla, Joebit C. (April 2009)
The rheological behavior of vacuum-concentrated kalamansi juice and sugar concentrated juice containing hydrocolloid was determined using an RVT rotational viscometer at rotational speeds of 5, 10, 20, 50, and 100 rev min -1. The vacuumconcentrated juice has total soluble solids of 50, 55, and 60 ˚Brix while the juice with hydrocolloid has xanthan gum concentrations of 0.2, 0.3, and 0.4 % (w/w). The speed and torque (0-100% on the scale) readings obtained from rotational viscometer with disc-type spindles were converted into viscosity functions to yield power law constants and shear rate- shear stress data. The analysis of the log shear stress - log speed dependence by linear regression indicated that this conversion was satisfactory (in all cases, with correlation coefficient r2> 0.9512). The power law and Herschel-Bulkley model were employed in the process to determine the consistency index and flow behavior index.
All samples exhibited pseudo-plasticity and were adequately described by the Herschel_Bulkley model within the temperature range of 25 - 80 ˚C. However, at temperatures above 50 ˚C, sugar-concentrated juice samples with 0.2 and 0.3 % xanthan gum were described by the power law model because of the absence of yield stress. The magnitude of the flowindex was between 0.6119 - 0.8995 and 0.4496 - 0.8832 for vacuum - and sugar-concentrated kalamansi juice, respectively. The magnitude of consistency index decreased with increase in temperature and increased with increase in concentration. The apparent viscocity decreased with increase in temperature and the effect was described well by the Arrhenius type equation. Depending on the concentration, the magnitude of activation energies at 100 rev min -1 for sugar-concentrated kalamansi mixed with xanthan gum varied from 9.60 x 10 3 to 1.15 x 10⁴ J mol-1 while the activation energies for vacuum-concentrated kalamansi varied from 2.26 x 10⁴ to 2.55 x 10⁴ J mol -1. The effect of totral soluble solids of vacuum concentrated kalamansi on apparent viscosity was also studied using the exponential type equation. However for practical purposes, expressions were obtained at each viscometer speed (5, 10, 20, 50, 100 rpm) for the combined effect of soluble solids concentration and temperature on the apparent viscosity of vacuum-concentrated kalamansijuice. At 100 rev min -1, the resulting expression is as follows: Π100 = 1.62 -3 exp (0.0599C +2833/T.
Thesis (M.S. in Chemical Engineering)--University of the Philippines Diliman.
Keywords: Hydrocolloid